Physical activity of children and adolescents who use a wheelchair: a systematic review - Selina Seemüller; Franziska Beck; Anne Kerstin Reimers (BMC Public Health, 2023)
Abstract Physical activity has numerous health benefits for people with physical disabilities. Nevertheless, activity levels are often below recommended levels. To promote physical activity among children and adolescents who use a wheelchair as their primary source of mobility, this systematic review explores the physical activity patterns of this group. A systematic search of PubMed, Sports Medicine & Education Index, Web of Science, and SPORTDiscus was performed, included articles were synthesized in terms of duration, intensity, and settings in which physical activity occurred, as well as the physical activity measurement methods. Nine articles were included. The mean overall physical activity level across the included studies was 98 minutes per day (range: 78–115 minutes per day). Two articles analysed the duration of physical activity at different intensities (very light physical activity, light physical activity (LPA), moderate to vigorous physical activity (MVPA) and intensities near to maximum). Within the included articles, both subjective and objective measurement methods were used. Due to the small number of articles, combined with small sample sizes, there is not enough evidence to answer the research questions sufficiently. Nevertheless, the review provides an overview of actual research and clearly shows that the physical activity values are insufficiently researched. There is a need for further research on the scope, types and settings of physical activity in the target group.